Diferences between the sexes in femicide - Vallejo, Paula (Estrategias. Psicoanálisis y salud mental, 2016)
Femicide should be thought as one way in which the discontent in today civilization is shaped. The subject is not longer satisfied by the phantom dream but is likely to fulfill it.